Comparative proteome and transcriptome analysis of lager brewer's yeast in the autolysis process. Issue 8 (1st December 2014) - Xu, Weina; Wang, Jinjing; Li, Qi
Abstract: The autolysis of brewer's yeast during beer production has a significant effect on the quality of the final product. In this work, we performed proteome and transcriptome studies on brewer's yeast to examine changes in protein and mRNA levels in the process of autolysis. Protein and RNA samples of the strain Qing2 at two different autolysis stages were obtained for further study. In all, 49 kinds of proteins were considered to be involved in the autolysis response, eight of which were up-regulated and 41 down-regulated. Seven new kinds of proteins emerged during autolysis. Results of comparative analyses showed that important changes had taken place as an adaptive response to autolysis. Functional analysis showed that carbohydrate and energy metabolism, cellular amino acid metabolic processes, cell response to various stresses (such as oxidative stress, salt stress, and osmotic stress), translation and transcription were repressed by the down-regulation of the corresponding proteins, and starvation and DNA damage responses could be induced. The comparison of data on transcriptomes with proteomes demonstrated that most autolysis-response proteins as well as new proteins showed a general correlation between mRNA and protein levels. Thus these proteins were thought to be transcriptionally regulated. These findings provide important information about how brewer's yeast acts to cope with autolysis at molecular levels, which might enhance global understanding of the autolysis process. Results of proteome and transcriptome analysis provide important information about how brewer's yeast acted to cope with autolysis at molecular levels, which might enrich the global understanding of autolysis process. Results of proteome and transcriptome analysis provide important information about how brewer's yeast acted to cope with autolysis at molecular levels, which might enrich the global understanding of autolysis process.